Answer:
To find the product of (x-3)(x^2+3x+9), we can use the distributive property of multiplication over addition. We will multiply each term in the first expression, (x-3), by each term in the second expression, (x^2+3x+9).
Let's break it down step by step:
1. Start with the first term, x, in the first expression, (x-3). Multiply it by each term in the second expression, (x^2+3x+9):
- x * x^2 = x^3
- x * 3x = 3x^2
- x * 9 = 9x
2. Move on to the second term, -3, in the first expression, (x-3). Multiply it by each term in the second expression, (x^2+3x+9):
- (-3) * x^2 = -3x^2
- (-3) * 3x = -9x
- (-3) * 9 = -27
3. Now, let's combine the like terms obtained in the previous steps:
- x^3 + 3x^2 + 9x - 3x^2 - 9x - 27
4. Simplify by combining like terms:
- x^3 + 3x^2 - 3x^2 + 9x - 9x - 27
- x^3 - 27
So, the product of (x-3)(x^2+3x+9) is x^3 - 27.